Prevalence of ocular morbidity among children aged 17 years or younger in the eastern India - Rao, G Nageswar (Clin Ophthalmol, 2018)
PURPOSE: Childhood ocular morbidity involves a spectrum of eye diseases that critically impact the mental development, future education and quality of life. However, there is limited evidence about the early detection and appropriate treatment of ocular morbidity in children <20 years. This study was aimed to assess the prevalence and make a comparison between the different types of ocular morbidity in children of both sexes in the age group of 6–17 years in the eastern India. METHODS: A cross-sectional survey of ocular morbidity among children <17 years of age who presented at the Department of Ophthalmology, Kalinga Institute of Medical Sciences, Bhubaneswar, and Vision Care Center for Retina, Bhubaneswar, in the eastern India between January 2015 and March 2018 was accomplished. Demographic information, visual acuity, type of eye injury, refractive errors and other detailed ophthalmic examination were screened. RESULTS: A total of 633 children (age 6–17 years) were examined in this study. The majority of cases were observed in children of age 12–17 years, accounting for almost close to half of all the cases. The prevalence of ocular morbidity was 45.92% in males and 53.97% in females. The most common ocular morbidity in children encountered was refractive error (54.62%), followed by congenital abnormalities (9%), allergic conjunctivitis (8.52%) and traumatic eye injury (7.1%). There was an increase in ocular morbidity with age, especially the refractive error and congenital abnormalities. CONCLUSION: A large number of ocular morbidity was observed in children of age <17 years. Since most of this morbidity was preventable or treatable, reasonable service for ocular morbidity and early age screening are effective methods to reduce this load. Moreover, health education for the prevention of childhood ocular morbidity and, at the same time, early presentation of children to ophthalmic hospitals for the treatment of eye disorders are essential.